Spatial spread of Wolbachia in Rhagoletis cerasi populations. (23rd May 2018) - Bakovic, Vid; Schebeck, Martin; Telschow, Arndt; Stauffer, Christian; Schuler, Hannes
Abstract : The bacterial endosymbiont Wolbachia has been used to control insect pests owing to its ability to manipulate their life history and suppress infectious diseases. Therefore, knowledge on Wolbachia dynamics in natural populations is fundamental. The European cherry fruit fly, Rhagoletis cerasi, is infected with the Wolbachia strain w Cer2, mainly present in southern and central European populations, and is currently spreading into w Cer2-uninfected populations driven by high unidirectional cytoplasmic incompatibility. Here, we describe the distribution of w Cer2 along two transition zones where the infection is spreading into w Cer2-uninfected R. cerasi populations. Fine-scale sampling of 19 populations in the Czech Republic showed a smooth decrease of w Cer2 frequency from south to north within a distance of less than 20 km. Sampling of 12 Hungarian populations, however, showed a sharp decline of w Cer2 infection frequency within a few kilometres. We fitted a standard wave equation to our empirical data and estimated a Wolbachia wave speed of 1.9 km yr −1 in the Czech Republic and 1.0 km yr −1 in Hungary. Considering the univoltine life cycle and limited dispersal ability of R. cerasi, our study highlights a rapid Wolbachia spread in natural host populations.